Ethnobotany of medicinal plants used to treat skin wounds in two rural communities in the region of Baixo Tocantins, Amazon, Brazil (Research, Society and Development, 2021)
Ethnobotanical surveys of medicinal plants with the potential to heal skin wounds can be an alternative to aid this care or accelerate the healing process and for the pharmaceutical industry are important in the choice of species to invest in laboratory tests. In this context, the research aimed to conduct an ethnobotanical survey of medicinal plants used by residents of two rural communities in the Brazilian Amazon for the treatment of skin wounds, in addition to recording the indications, uses and ways of preparing homemade formulations. The snowball was adopted as a methodology to select employees and ethnobotanical techniques for data collection. The importance of each species was determined by calculating the relative frequency of citation (RFC). In total, 17 employees participated and knowledge of 16 ethnospecies used in the healing process of skin wounds was recorded. The highest CRF values ​​recorded were for the species of andiroba (Carapa guianensis Aubl.), copaiba plant (Escobedia sp.) And malvarisco (Piper umbellatum L.). As a result, it is noteworthy that the medicinal plants used in these communities contribute to improving the quality of life and are important for the treatment of skin wounds.